Overview of the Arctic Challenge for Sustainability (ArCS) project (2015-2020) - Fukasawa, Masao (2020)
The 11th Symposium on Polar Science/Special session: [S] Accelerating Arctic research: Recent progress and future prospect of Arctic research, Tue. 1 Dec. conference object